The economics of mobile telecommunications - Gruber, Harald (Cambridge University Press, 2005)
Offers a comprehensive economic analysis of the main determinants of growth in the mobile telecommunications industry. Detailed country studies provide empirical evidence for the development of the main themes. This research-based survey will appeal to a wide range of applied industrial economists within universities, government and the industry itself.